2014
DOI: 10.1182/blood-2014-06-583294
|View full text |Cite
|
Sign up to set email alerts
|

Ibrutinib treatment affects collagen and von Willebrand factor-dependent platelet functions

Abstract: Key Points• Ibrutinib affects collagen and VWF-mediated platelet activation.• The bleeding diathesis correlates with defects in collagen-induced platelet aggregation and firm adhesion on VWF at arterial shear rate.The oral Bruton's tyrosine kinase inhibitor, ibrutinib, has recently demonstrated high efficiency in patients with relapsed B-cell malignancies. Occurrence of bleeding events has been reported in a subgroup of ibrutinib-treated patients. We demonstrate that ibrutinib selectively inhibits platelet sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
260
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(281 citation statements)
references
References 19 publications
14
260
0
2
Order By: Relevance
“…Concordant with recent reports implicating impaired collagen-induced platelet aggregation (assessed by formal platelet aggregation testing) as the likely cause of ibrutinib-associated bleeding, [2][3][4] the authors performed platelet aggregometry in 12 normal subjects, 14 subjects with treatment-naïve CLL, and 30 ibrutinib-treated subjects with CLL. In contradistinction to earlier reports, Lipsky et al found that patients with untreated CLL had significant baseline impairments in platelet aggregation to collagen and ADP, and that patients taking ibrutinib had a modest further reduction in collageninduced platelet aggregation, but an improvement in ADPinduced platelet aggregation.…”
supporting
confidence: 52%
See 1 more Smart Citation
“…Concordant with recent reports implicating impaired collagen-induced platelet aggregation (assessed by formal platelet aggregation testing) as the likely cause of ibrutinib-associated bleeding, [2][3][4] the authors performed platelet aggregometry in 12 normal subjects, 14 subjects with treatment-naïve CLL, and 30 ibrutinib-treated subjects with CLL. In contradistinction to earlier reports, Lipsky et al found that patients with untreated CLL had significant baseline impairments in platelet aggregation to collagen and ADP, and that patients taking ibrutinib had a modest further reduction in collageninduced platelet aggregation, but an improvement in ADPinduced platelet aggregation.…”
supporting
confidence: 52%
“…Remaining mindful of ibrutinib's property as a potent, irreversible anti-platelet drug is highly useful in the clinic, particularly in the management of patients with severe thrombocytopenia and/or taking multiple antiplatelet agents, and in the treatment of patients presenting with acute bleeding or requiring emergency surgery, where transfusion of fresh platelets outside the 3 -4 hour ibrutinib plasma half-life window completely reverses the bleeding phenotype. 3 We and others have observed baseline defects in platelet aggregation in patients with CLL.…”
mentioning
confidence: 99%
“…The contribution of TEC to collagen signalling in the presence of BTK seems to be minor, as platelets from TEC KO mice have only a slight defect in the aggregation response to collagen 65. Platelet activation by vWF, the other activation pathway that is affected by ibrutinib treatment 20, also involves BTK 80. So far, no role for TEC has been described in this process, but it does not seem to compensate for absent BTK, because no phosphorylation of PLC γ 2 was found in platelets from BTK‐deficient mice after vWF stimulation, and no stable vWF‐dependent thrombus formation was observed in vivo in these mice 81.…”
Section: Consequences Of Ibrutinib Treatment Not Related To B Cellsmentioning
confidence: 99%
“…Several labs have shown that ibrutinib can impair platelet activation in vitro, 4,5 and platelets taken from ibrutinibtreated patients have an impaired response to collagen and reduced adhesion to von Willebrand Factor (vWF) ex vivo. 6,7 It has therefore been suggested that ibrutinibinduced platelet dysfunction underlies bleeding in patients. In contrast, administration of ibrutinib analogs in non-human primates had no significant effect on bleeding time despite the ability to inhibit collagen-mediated platelet activation in vitro and ex vivo following treatment.…”
mentioning
confidence: 99%